2011
DOI: 10.1088/0004-637x/729/2/80
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Axisymmetric Transport of Magnetic Elements on the Sun: 1996-2010

Abstract: We measure the axisymmetric transport of magnetic flux on the Sun by cross-correlating narrow strips of data from line-of-sight magnetograms obtained at a 96 minute cadence by the MDI instrument on the ESA/NASA SOHO spacecraft and then averaging the flow measurements over each synodic rotation of the Sun. Our measurements indicate that the axisymmetric flows vary systematically over the solar cycle. The differential rotation is weaker at maximum than at minimum. The meridional flow is faster at minimum and slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
81
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 50 publications
19
81
0
4
Order By: Relevance
“…The meridional flow speed measurements of Ulrich (2010), Basu and Antia (2010) and Hathaway and Rightmire (2011) do not show evidence of significantly faster flows at active latitudes during cycle 23 than during previous cycles. Moreover, Basu and Antia (2010) concluded that the flow speed variation reported by Hathaway and Rightmire (2010) was associated with a flow pattern that migrated equatorward with the magnetic activity belts.…”
Section: Unusual Cycle 23 Minimummentioning
confidence: 58%
“…The meridional flow speed measurements of Ulrich (2010), Basu and Antia (2010) and Hathaway and Rightmire (2011) do not show evidence of significantly faster flows at active latitudes during cycle 23 than during previous cycles. Moreover, Basu and Antia (2010) concluded that the flow speed variation reported by Hathaway and Rightmire (2010) was associated with a flow pattern that migrated equatorward with the magnetic activity belts.…”
Section: Unusual Cycle 23 Minimummentioning
confidence: 58%
“…For instance, the results of Hathaway (2010) indicate that the meridional flow speed during the decay phase of cycle 23 was nearly 20% higher than during the corresponding phase in cycle 22. Furthermore, the meridional flow profile used in the flux transport simulation probably underestimates the poleward velocities beyond 60 • latitude (Hathaway and Rightmire 2011). On the other hand, polar countercells of the meridional flow could redistribute flux from the polar cap to lower latitudes and thus also contribute to weaker polar fields (Jiang et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…We know the value of both Ω| R NSSL and Ω| R from observations. For the surface rotation rate we use the synodic rate for magnetic fields of Hathaway & Rightmire (2011), Ω| R = 14.30 − 1.98 cos 2 θ − 2.14 cos 4 θ [ • /day]. (A.10)…”
Section: Appendix A: Generation Of Toroidal Flux By Differential Rotamentioning
confidence: 99%